Liszt and Mahler in the postmodern fi lmic visions of Ken Russell - Golianek, Ryszard Daniel (Katedra Muzykologii, Wydawnictwo Naukowe PTPN, Wydawnictwo Naukowe UAM, 2013)
The British fi lm and television director Ken Russell is esteemed principally for creating fi lmic biographies of composers of classical music. In the 70s, he shot his most original fi lms on musical subjects: fi ctionalised, highly individual composer biographies of Mahler (Mahler) and Liszt (Lisztomania), which are the subject of the article. Neither of the fi lms is in the least a realistic documentary biography, since Russell’s principal intention was to place historical biographical facts in cultural contexts that were diff erent from the times in which Mahler and Liszt lived and worked. This gave rise to a characteristically postmodern collision of diff erent narrative and expressive categories. Russell’s pictures remain quite specifi c commercial works, exceptional tragifarces, in which the depiction of serious problems is at once accompanied by their subjection to grotesque deformation and the demonstration of their absurdities or denaturalisation. The approach proposed by this British director, in which serious issues are accompanied by elements of triteness, is a hallmark of his style. The director’s musical interests are refl ected by the fundamental role of music in the structure of his cinematographic works. The choice of musical works also denotes a kind of aesthetic choice on the director’s part, especially when the composers’ biography comes into play.
Keywords: Ken Russell; Gustav Mahler; Franz Liszt; film; postmodern